Rent taxes on natural resources in Norway: A short overview - Eirik S. Amundsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2024)
For a long time, Norway has had resource rent taxes on oil- and natural gas extraction as well as on hydropower generation. Recently, resource rent taxes have also been levied on aquaculture, and wind power generation. This paper, gives a short overview of the rent theory, the basis for rent generation in Norway, the size of rent generated, the Norwegian tax system for resource rent for each of the resources considered, and the rent taxes collected.
Keywords: H20; H25; Q22; Q25; Q38; Q48; 330; Natural resources; economic rent; resource rent tax; Norway